Balancing Sanctions and Civilian Protection: Evaluating Humanitarian Carve-Outs under International Humanitarian Law - Widaningsih (Legalis : Journal of Law Review, 2025)
Sanctions are widely used to enforce international norms, including International Humanitarian Law (IHL), but their unintended humanitarian consequences—especially for health systems and aid access—are increasingly evident. This study evaluates whether humanitarian carve-outs introduced under UN Security Council Resolution 2664 have mitigated these impacts. Using a Difference-in-Differences (DiD) framework, it analyzes data from 120 sanctioned countries (2000–2023), drawing from the Global Sanctions Database (GSDB-R4), WHO, UN IGME, and UNSC Panel of Experts reports. The treatment variable is the presence of humanitarian carve-outs, while outcome measures include under-five mortality rate (U5MR), maternal mortality, and aid delivery delays. Results show that carve-outs significantly reduced average aid delivery delays—from 22 to 13 days—and improved U5MR by approximately 8–10% in post-carve-out periods. No significant effect was observed on maternal mortality. Multilateral sanctions regimes implemented carve-outs more effectively than unilateral ones. Case studies from Yemen and Sudan confirmed operational improvements, whereas the Democratic Republic of the Congo (DRC) revealed persistent compliance and enforcement challenges. Over-compliance by banks and inconsistent national regulations continue to hinder humanitarian operations. The study concludes that humanitarian carve-outs represent a meaningful advance in aligning sanctions policy with civilian protection. However, their long-term effectiveness depends on legal clarity, multilateral coordination, and real-time monitoring. Policy recommendations include standardized implementation guidelines, safe harbor provisions for financial institutions, and greater inclusion of local actors to ensure sanctions enforcement does not exacerbate human suffering.